Characteristics of Pediatric Patients with Diarrhea in Indonesia: A Laboratory-based Report - Lia Amanda; Karin Nadia Utami; Andria Amanda Pulungan; Diar Riyanti Rudiatmoko; Fatima Safira Alatas (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Background: Diarrhea is still a common health problem in Indonesia, with high morbidity and mortality rate. The severity of diarrhea is associated with age, nutritional status, and cause of diarrhea. This study aims to describe the characteristics and laboratory findings, particularly stool analysis, in pediatric patients with diarrhea. Methods: A retrospective study was conducted using data from patients aged 0 to 18 with diarrhea who underwent stool analysis in Cipto Mangunkusumo Hospital between 2012 and 2016. Results: The average age of children with diarrhea was 45 months, with most patients (55,6%) being under two years old children. More than half of the patients were boys (58.8%). Two-thirds of the patients (67%) presented with watery stool diarrhea. The interpretation of stool analysis indicated that nearly half of the patients (48%) experienced diarrhea due to bacterial infection, followed by fat malabsorption (20.8%). Similar results were also seen in the stool analysis of children aged 0-24 months, with the prevalence of bacterial infection (35.2%) and fat malabsorption (30.2%) being the most commonly identified etiology of diarrhea. Conclusion: In Indonesia, children under two and male gender were more frequently reported to experience diarrhea. The primary manifestation of pediatric diarrhea was watery stools, while the most common etiology was bacterial infections.